Spirits in the first-century Jewish world, Luke-Acts and in the African context: an analysis - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Thesis (PhD (New Testament Studies))--University of Pretoria, 2006.